Paul and the resurrection of Israel: Jews, former gentiles, Israelites - Staples, Jason A. (Cambridge University Press, 2024)
The gospel promoted by Paul has for many generations stirred passionate debate. That gospel proclaimed equal salvific access to Jews and gentiles alike. But on what basis? In making sense of such a remarkable step forward in religious history, Jason Staples reexamines texts that have proven thoroughly resistant to easy comprehension. He traces Paul's inclusive theology to a hidden strand of thinking in the earlier story of Israel. Postexilic southern Judah, he argues, did not simply appropriate the identity of the fallen northern kingdom of Israel. Instead, Judah maintained a notion of 'Israel' as referring both to the north and the ongoing reality of a broad, pan-Israelite sensibility to which the descendants of both ancient kingdoms belonged. Paul's concomitant belief was that northern Israel's exile meant assimilation among the nations - effectively a people's death - and that its restoration paradoxically required gentile inclusion to resurrect a greater 'Israel' from the dead.